Lords of finance : the bankers who broke the world - Ahamed, Liaquat (New York : Penguin Press, 2009)
With penetrating insights for today, this vital history of the world economic collapse of the late 1920s offers portraits of four men--Montagu Norman, Amile Hilaire Emile Moreau, Hjalmar Horace Greeley Schacht, and Benjamin Strong--whose personal and professional actions as heads of their respective central banks changed the course of the twentieth century.
-- part 1. The unexpected storm, August 1914. -- Prologue -- A strange and lonely man -- The young wizard -- A safe pair of hands -- L'inspecteur des finances -- Money generals -- part 2. After the deluge, 1919-23. -- Demented inspirations -- Uncle Shylock -- A barbarous relic -- part 3. Sowing a new wind, 1923-28. -- A bridge between chaos and hope -- The Dawes opening -- The golden chancellor -- La Bataille -- The first squalls -- Un petit coup de whisky -- part 4. Reaping another whirlwind, 1928-33. -- Into the vortex -- Purging the rottenness -- Magneto trouble -- A loose cannon on the deck of the world -- Gold fetters -- part 5. Aftermath, 1933-1944. -- Gold standard on the booze -- The caravans move on -- Epilogue.
Includes bibliographical references (pages [533]-544) and index.
Keywords: Norman, Montagu, -- 1871-1950; Moreau, Emile, -- 1868-1950; Schacht, Hjalmar Horace Greeley, -- 1877-1970; Strong, Benjamin, -- 1872-1928; Capitalists and financiers -- Biography; Bankers -- Biography